Pengaruh Return On Asset, Return On Equity dan Net Profit Margin Terhadap Harga Saham - Daniel Ramos Simbolon; Sri Suartini (COSTING : Journal of Economic, Business and Accounting, 2021)
In an era of globalization like this, the growing public interest in automotive and components in Indonesia, companies should carry out better corporate governance to face competition. This study aims to examine the effect of ROA, ROE, and NPM on stock prices in automotive and component manufacturing companies listed on the IDX for the 2014-2019 period. Sampling using purposive sampling and obtained 5 automotive subsector companies and components from 13 automotive subsector companies and components as samples. So that the number of samples studied is 30 data for 6 years. The research method used is quantitative research methods with descriptive and verification approaches. Based on the results of research conducted by the author using SPSS 20, it can be concluded with the t test and f test, namely: ROA has a negative effect on stock prices, ROE has no effect on stock prices, NPM has a positive effect on stock prices. Simultaneously ROA, ROE and NPM have an effect on stock prices. Based on the determinant coefficient test, it was found that the independent variable affected the dependent by 55.7% and there were still 44.3% other factors outside the independent variable in this study. Keywords: ROA, ROE, NPM, Stock Price.